ECONOMIC FOUNDATIONS OF ISLAM - Aly, Mr. Syed (Dirasat in Economics and Business, 1966)
This book has been a recent addition to the University Library, Benghazi, authored by Mr. Syed Ahmed Aly B.Sc. (econ.) London, and F.R. Econs and who is now on the academic staff of the Libyan University, Faculty of Commerce. The author joined the Patna University in 1941. He has toured the Middle East, Europe, Canada, U.S.A., moreover, he served with the International Commission in Loas and wrote an interesting "Econormc Report on Laos' To Mr. Syed Ali, Humanism and Islam are interchangeable. He felt the lack of a book about Islam that dealt fairly with the subject, based on the study of the Koran, its commentaries and reliable traditions. He has spared no effort, time or money to dig for the facts, his criteria being quality, authenticity and reasonableness of material. His aim is to present the pure Islamic thought in social and economic matters. He sees Islam as neither patterned after anv economic norm, nor based on laissez-faire theory or totalitarianism. The author seeks to prove his theory that Islam can serve the purpose of a modern social and economic system. He traces Islam through the ages since its dawn in the 7th Century. Chapter Two deals with the foundation of social and economic order, giving an account of its postulates, Chapter Three presents a resumé of the struggle for existence. Man is taught to adiust himself to nature